Genetic pathway analysis reveals a major role for extracellular matrix organization in inflammatory and neuropathic pain. Issue 4 (April 2019) - Parisien, Marc; Samoshkin, Alexander; Tansley, Shannon N.; Piltonen, Marjo H.; Martin, Loren J.; El-Hachem, Nehme; Dagostino, Concetta; Allegri, Massimo; Mogil, Jeffrey S.; Khoutorsky, Arkady; Diatchenko, Luda
Abstract : Abstract: Chronic pain is a debilitating and poorly treated condition whose underlying mechanisms are poorly understood. Nerve injury and inflammation cause alterations in gene expression in tissues associated with pain processing, supporting molecular and cellular mechanisms that maintain painful states. However, it is not known whether transcriptome changes can be used to reconstruct a molecular pathophysiology of pain. In the current study, we identify molecular pathways contributing to chronic pain states through the analysis of global changes in the transcriptome of dorsal root ganglia, spinal cord, brain, and blood in mouse assays of nerve injury– and inflammation-induced pain. Comparative analyses of differentially expressed genes identified substantial similarities between 2 animal pain assays and with human low-back pain. Furthermore, the extracellular matrix (ECM) organization has been found the most commonly regulated pathway across all tested tissues in the 2 animal assays. Examination of human genome-wide association study data sets revealed an overrepresentation of differentially expressed genes within the ECM organization pathway in single nucleotide polymorphisms most strongly associated with human back pain. In summary, our comprehensive transcriptomics analysis in mouse and human identified ECM organization as a central molecular pathway in the development of chronic pain. Abstract : Supplemental Digital Content is Available in the Text.The extracellular matrix organization pathway was found a major contributor to both inflammatory and chronic pain etiologies, including risk for back pain from human genome-wide association study.